Topiramate Reprofiling for the Attenuation of Cadmium-Induced Testicular Impairment in Rats: Role of NLRP3 Inflammasome and AMPK/mTOR-Linked Autophagy - Hany H. Arab; Hayat A. Abd El Aal; Shuruq E. Alsufyani; Azza A. K. El-Sheikh; El-Shaimaa A. Arafa; Ahmed M. Ashour; Ahmed M. Kabel; Ahmed H. Eid (MDPI AG, 2022)
Topiramate, a promising drug classically used for the management of neurological disorders including epilepsy and migraine, has demonstrated marked anti-inflammatory and anti-apoptotic actions in murine models of cardiac post-infarction inflammation, wound healing, and gastric/intestinal injury. However, its potential impact on cadmium-induced testicular injury remains to be elucidated. Herein, the present study aimed to explore the effect of topiramate against cadmium-invoked testicular impairment with emphasis on the molecular mechanisms linked to inflammation, apoptosis, and autophagy. Herein, administration of topiramate (50 mg/kg/day, by gavage) continued for 60 days and the testes were examined by histology, immunohistochemistry, and biochemical assays. The present data demonstrated that serum testosterone, sperm count/abnormalities, relative testicular weight, and histopathological aberrations were improved by topiramate administration to cadmium-intoxicated rats. The rescue of testicular dysfunction was driven by multi-pronged mechanisms including suppression of NLRP3/caspase-1/IL-1β cascade, which was evidenced by dampened caspase-1 activity, lowered IL-1β/IL-18 production, and decreased nuclear levels of activated NF-κBp65. Moreover, curbing testicular apoptosis was seen by lowered Bax expression, decreased caspase-3 activity, and upregulation of Bcl-2. In tandem, testicular autophagy was activated as seen by diminished p62 SQSTM1 accumulation alongside Beclin-1 upregulation. Autophagy activation was associated with AMPK/mTOR pathway stimulation demonstrated by decreased mTOR (Ser2448) phosphorylation and increased AMPK (Ser487) phosphorylation. In conclusion, combating inflammation/apoptosis and enhancing autophagic events by topiramate were engaged in ameliorating cadmium-induced testicular impairment.